2017
DOI: 10.1177/2325967117728684
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Shoulder Rotational Muscle Strength After Arthroscopic Bankart Repair

Abstract: Background:Shoulder rotational muscles act as dynamic stabilizers of the glenohumeral joint, and the recovery of muscle strength plays an important role in stabilizing the joint during postoperative rehabilitation. However, temporal changes in muscle strength after arthroscopic Bankart repair have not been clarified.Purpose:To better understand the temporal recovery of shoulder rotational muscle strength after arthroscopic Bankart repair.Study Design:Case series; Level of evidence, 4.Methods:Isokinetic concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Literature states that that women are more muscle fatigue resistant than men [30,31]; however, this assumption requires further research. Comparable relation was stated by Amako et al In their research agon/antagon ratio was lower than reference values as well [2]. Tahta et al found opposite relationship-internal rotation strength was lower than external rotation strength which results in a several hundred percent values of ratio [8].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Literature states that that women are more muscle fatigue resistant than men [30,31]; however, this assumption requires further research. Comparable relation was stated by Amako et al In their research agon/antagon ratio was lower than reference values as well [2]. Tahta et al found opposite relationship-internal rotation strength was lower than external rotation strength which results in a several hundred percent values of ratio [8].…”
Section: Discussionmentioning
confidence: 71%
“…They suggested that return of full muscle strength was possible after 9-12 months. Amako et al assessed results of arthroscopic stabilization as well indicating faster recovery of internal rotation (IR) compared to external rotation (ER) [2]. Tatha et al described persistent loss of ER strength 12 months after arthroscopic stabilization [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoulder and glenohumeral instability are a serious problem for athletes and military personnel [1][2][3][4][5][6]. These younger, more active populations are at high risk for glenohumeral instability with military personnel sustaining shoulder dislocations at a greater rate compared to the overall United States (U.S.) population (3.13 per 1,000 person years) [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder and glenohumeral instability are serious problems for athletes and military personnel [1][2][3][4][5][6]. In general, younger and more active populations are at a high risk for glenohumeral instability [2].…”
Section: Introductionmentioning
confidence: 99%